2020
DOI: 10.3390/su12020623
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Regulations on Environmental Quality and Public Health in China: Empirical Analysis with Panel Data Approach

Abstract: Achieving high-quality environmental development through environmental regulations and thus enhancing public health is a goal of the Chinese government. Based on the panel data of 30 Chinese provinces from 1998 to 2017, this study demonstrates the co-benefits of environmental regulations on air quality, water, and public health through a panel Granger causality model and mediation effect model. The findings indicate that environmental regulations have a Granger causal effect on public health costs and air and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Ref. [9] analysed the influence of environmental regulations on public health costs and air and water pollution using Granger causality tests. The results showed that environmental regulation has important common benefits for high-quality environmental development and public health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ref. [9] analysed the influence of environmental regulations on public health costs and air and water pollution using Granger causality tests. The results showed that environmental regulation has important common benefits for high-quality environmental development and public health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…McGartland et al ( 23 ) estimated the health benefits of environmental regulations and concluded that reductions in various environmental pollutants can have a beneficial effect on non-cancer health. Tang et al ( 24 ) came to the conclusion that environmental regulations have a significant co-benefit on high-quality environmental development and public health. However, some studies have also concluded that the policy effects of environmental regulation are limited.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Therefore, we need to calculate the correlation between different indicators, from which we can select the appropriate characteristics for water quality assessment. Commonly used correlation analysis methods include Pearson correlation coefficient analysis ( Zhang et al., 2022a ), Granger causality analysis ( Tang et al., 2020 ), and grey relational analysis ( Wang et al., 2020 ). Most indicators affecting water quality are grey and localized.…”
Section: Introductionmentioning
confidence: 99%